Micronutrients Intake and Exclusive Breastfeeding as a Risk Factor for Stunting among Children Aged 13-36 Months Old in Simpang Kiri, Subulussalam - Lestari, Wanda; Angkat, Abdul Hairuddin (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Stunting is a state of the nutritional status of a person based on the z-score height of age which lies in z-score <-2 SD. Stunting is a state of undernutrition that continues over time and happens in the long term. Prevalence of stunting in Subulussalam among children under 5 years old was is 64,91% which 48% occured in Simpang Kiri sub-district. This study was aimed to analyze whether micronutrient intake and exclusive breastfeeding were risk factors for stunting. The design was case-control unmatched, the subjects were children between 12-36 months with 53 stunted and 55 normal. The variables were the frequency of intake mineral source (Ca, Fe, and Zn), the frequency of intake vitamin A source, and exclusive breastfeeding. Data were analyzed using chi-square test and odds ratio.The results showed that frequency of intake Ca source (OR=4,11, 95%CI:1,83-9,25), frequency of intake Fe source (OR=4,31, 95%CI:1,70-10,9), frequency of intake Zn source (OR=7,46, 95%CI: 1,58-35,2), frequency of intake vitamin A source (OR=2,51, 95%CI: 1,15-5,49) and exclusive breastfeeding (OR=5,38, 95%CI:2,28-12,7) were the risk factor against stunting. Intake of micronutrients (calcium, Fe, zinc, and Vitamin A) and exclusive were a risk factors for stunting